The Effect Of Compliance In The Use Of Clinical Pathway (CP) And Duration Of Care On Cost Efficiency In Patients With Caesarian Section (SC) - Habibah, Zahrotul; Purwadhi, Purwadhi; Handayani, Nining (JKM (Jurnal Kebidanan Malahayati), 2024)
Clinical Pathway (CP) penting untuk mengurangi biaya, lama perawatan serta dapat meningkatkan mutu pelayanan pasien, terutama pada era asuransi Jaminan Kesehatan Nasional (JKN). Tujuan studi ini adalah untuk mengetahui pengaruh angka kepatuhan terhadap CP dan lama perawatan terhadap efisiensi biaya perawatan pasien sectio cesarean (SC). Studi cross sectional menggunakan data primer di RS Edelweiss bulan Juli-September 2024. Tingkat kepatuhan CP berkorelasi positif secara signifikan terhadap GPM (r=0.558, p<0.001), dan lama perawatan berkorelasi secara negatif secara signifikan terhadap GPM (r=-0.467, p<0.001). Hasil analisa regresi linier didapatkan tingkat kepatuhan CP dan lama perawatan secara simultan mempengaruhi GPM (F=10,221, p<0.001). Kepatuhan terhadap penggunaan Clinical Pathway serta pengelolaan lama perawatan memiliki pengaruh yang signifikan terhadap efisiensi biaya pada pasien sectio caesarean (SC). Keunggulan dari penelitian ini yaitu relevansi topik yang diteliti dengan situasi manajemen RS saat ini dan menggunakan metode kuantitatif memungkinkan pengukuran yang objektif terhadap variabel-variabel yang diteliti, seperti biaya, lama perawatan, dan tingkat kepatuhan. Kata Kunci: kepatuhan terhadap clinical pathway, lama perawatan, efisiensi biaya ABSTRACT Clinical Pathways (CP) are crucial for reducing costs and length of stay while improving patient service quality, especially in the era of the National Health Insurance (JKN). This study aims to determine the effect of compliance rates with CP and length of stay on cost efficiency for patients undergoing cesarean section (CS). A cross-sectional study was conducted using primary data at Edelweiss Hospital from July to September 2024. A significant positive correlation was found between CP compliance and GPM (r=0.558, p<0.001), while length of stay had a significant negative correlation with GPM (r=-0.467, p<0.001). Linear regression analysis showed that both CP compliance and length of stay significantly influenced GPM (F=10.221, p<0.001). Compliance with the use of Clinical Pathways and management of length of stay significantly affects cost efficiency for patients undergoing cesarean section (CS) at Edelweiss Hospital Bandung. The excellence of this research is the relevance of the topic studied to the current hospital management situation and uses quantitative methods allowing objective measurements of the variables studied, such as costs, length of treatment, and level of compliance . Keywords: compliance of the use of clinical pathway, length of stay, cost efficiency  American Academy of Pediatrics (AAP), 2023. “Barriers and Facilitators of High-Efficiency Clinical Pathway Implementation in Hospitals.”Anderson, P., & Johnson, R. (2019). Clinical pathways: Are they really cost-saving? BMC Health Services Research , 19(2), 70-80.Anderson, P., & White, D. (2020). Does a longer hospital stay really save money? Journal of Health Services Research & Policy , 25(1), 50-60.Arbey, Muhammad., Purwadhi., Andriani, Rian., 2024. The Influence of the Quality of Outpatient Services of Specialist Doctors on the Satisfaction of BPJS Participant Patients. Case Study at Eko Maulana Ali Hospital, Bangka Regency. Horizon-IMWI RepositoryBai, J., Bai, F., Zhu, H., & Xue, D. (2018). The Perceived and Objectively Measured Effects of Clinical Pathways' Implementation on Medical Care in China . PLOS ONE , 13 (5).Bartlett, K. W., Parente, V. M., Morales, V., Hauser, J., & McLean, H. S. (2017). Improving the Efficiency of Care for Pediatric Patients Hospitalized With Asthma . Hospital Pediatrics, 7 (1), 31–38.Brown, T., & Williams, P. (2019). The relationship between length of stay and hospital costs: A retrospective analysis. Health Economics Review , 9(1), 15-25.Bryan, M.A., Desai, A.D., Wilson, L., Wright, D.R., & Mangione-Smith, R. (2017). Association of bronchiolitis clinical pathway adherence with length of stay and costs . Pediatrics, 139(3).Campbell, H., Hotchkiss, R., Bradshaw, N., & Porteous, M. (2009). Integrated care pathways. BMJ, 316(7125), 133-137.Chen, Y., & Nguyen, T. (2022). A meta-analysis of clinical pathways: Costs and outcomes. Health Economics Review , 12(1), 15-25.Chen, Y., & Nguyen, T. (2022). Length of stay as a determinant of healthcare costs: A meta-analysis. International Journal of Health Economics and Management , 22(1), 25-40.Creswell, J. W. (2014). Research Design: Qualitative, Quantitative, and Mixed Methods Approaches . Sage Publications.De Bleser, L., Depreitere, R., Waele, K., Vanhaecht, K., Vlayen, J., & Sermeus, W. (2006). Defining pathways. Journal of Nursing Management , 14(7), 553-563.Dey, B., Mitra, A., Prakash, K., Basu, A., Ray, S., & Mitra, A. (2013). Effectiveness of Care Pathways in Ideal Hospital Management System: A Review. Indo Global Journal of Pharmaceutical Sciences, 03 (03), 185–191.Eskandari, M., Alizadeh Bahmani, AH, Mardani-Fard, HA et al. Evaluation of factors that influence the length of hospital stay using data mining techniques. BMC Med Inform Decis Mak 22 , 280 (2022). https://doi.org/10.1186/s12911-022-02027-wFirdaus, R., & Nazaruddin, I. (2023). Relationship Between Clinical Pathway and Cost-Effectiveness Research Using Vosviewer: A Bibliometric Study . United International Journa l for Research & Technology , 4(03), 1–8.Firmansyah, Y., Bakhtiar, HS (2022). Implementation of the clinical pathway paradigm in achieving cost-effectiveness in health financing (systematic literature review) . Jurnal Medika Hutama, 3(2), 1855-1876.Fitria, A., Armani, AS, Rochmah, TN, Purwaka, BT, & Pudjirahardjo, WJ (2021). Implementation of Clinical Pathways as an Instrument for Controlling Service Costs: An Action Research Study of BPJS Patients Undergoing Caesarean Section with the INA-CBG Payment System. Silampari Nursing Journal, 4(2), 593–599.Fentiana, N., & Ginting, D. (2020). Hospital Revenue Increase Strategy Based on SWOT Analysis. Scientific Journal of Batanghari Jambi University, 20(3), 1008-1012.Garcia, R., & Chen, M. (2020). Assessing the economic impact of prolonged hospital stays on health care systems. Journal of Hospital Medicine , 15(4), 220-230.Ghaferi, A.A., Birkmeyer, J.D., & Dimick, J.B. (2021). The impact of clinical pathways on length of stay and costs in the surgical population. Journal of Surgical Research , 256, 369-376.Grimshaw, J.M., Thomas, R.E., MacLennan, G., Fraser, C., Ramsay, C.R., Vale, L., & Donaldson, C. (2004). Effectiveness and efficiency of guideline dissemination and implementation strategies. Health Technology Assessment, 8(6), iii-iv.Haninditya, Beta., Andayani, Tri Murti., Yasin, Nanang Munif. (2019). Analysis of Compliance in the Implementation of Clinical Pathway for Cesarean Section in a Private Hospital in Yogyakarta. JMPFHertler, A., Chau, S., Khetarpal, R., Bassin, E., Dang, J., Koppel, D. (2020). Utilization of Clinical Pathways Can Reduce Drug Spend Within the Oncology Care Model . JCO Oncology Practice, 16(5), ee456-e463.Horngren, CT, Datar, SM, & Rajan, MV (2012). Cost Accounting: A Managerial Emphasis. Pearson Education.Irwandy, I., & Sjaaf, AC (2018). Impact of National Health Insurance Policy on Hospital Efficiency: Case Study in South Sulawesi Province. Indonesian Public Health Media, Hasanuddin University, 14(4), 360-367.Iroth, JS, Ahmad, RA, & Pinzon, R. (2016). The Impact of Clinical Pathway Implementation on the Cost of Treatment for Acute Ischemic Stroke Patients at Bethesda Hospital, Yogyakarta. Duta Wacana Scientific Medical Journal, 2(1), 267─267.Jackson, T., & Brown, C. (2020). Questioning the benefits of clinical pathways in cost management. Journal of Clinical Outcomes Management , 27(4), 220-230.JAMA Network. (2021). “Interventions to Reduce Hospital Length of Stay in High-Risk Populations: A Systematic Review.”James, E., Rotter, T., & Snow, P. (2011). Evaluating the impact of clinical pathways on patient outcomes and hospital costs in an Australian hospital setting. Journal of Health Services Research & Policy, 16(4), 193-199.Jones, M., & Smith, R. (2021). The impact of clinical pathway compliance on hospital costs: A systematic review. Health Services Research , 56(3), 345-359.Johnson, L., & Green, R. (2020). Impact of length of stay on healthcare costs: a systematic review. Health Services Research , 55(3), 505-520.Kagedan, DJ, Devitt, K.S., Tremblay St-Germain, A., Ramjaun, A., Cleary, S.P., & Wei, A.C. (2017). The economics of recovery after pancreatic surgery: detailed cost minimization analysis of an enhanced recovery program . HPB, 19(11 ), 1026–1033.Kaplan, R. S., & Porter, M. E. (2011). How to solve the cost crisis in health care. Harvard Business Review.Lawal, A.K., Rotter, T., Kinsman, L., Machotta, A., Ronellenfitsch, U., Scott, S.D., Goodridge, D., Plishka, C., & Groot, G. (2016). What is a clinical pathway? Refinement of an operational definition to identify clinical pathway studies for a Cochrane systematic review. BMC Medicine, 14(1), 1─5.Lim, S.C., Doshi, V., Castasus, B., Lim, J.K., & Mamun, K. (2006). Factors causing delay in discharge of elderly patients in an acute care hospital. Annals of the Academy of Medicine, Singapore, 35(1), 27.Lorenzoni, L., & Marino, A. (2017 ). Understanding variations in hospital length of stay and costs: Results of a pilot project. OECD Health Working Papers No. 94, 1–43.Martin, J., & Chen, Y. (2023). Cost implications of clinical pathway adherence in surgical patients. Journal of Surgical Research , 250, 92-100.Martinez, F., & Kim, H. (2021). The impact of clinical pathways on healthcare expenditures: An empirical study. International Journal of Health Services , 51(3), 405-415.McKinsey & Company. (2023). "Clinical Pathways in European Healthcare: Lessons from Germany."MedBridge, 2022. "The Role of Clinical Pathways in Modern Healthcare Settings."MedBridge. (2022). "Clinical Pathways: Leading the Way to Better Outcomes."Miller, A., & Johnson, R. (2022). Cost implications of extended hospital stays for chronic illness management. International Journal of Health Services , 52(3), 340-355.Mustafa, A., Dwitasari, RN, Putra, SS, & Veranita, M., & Purwadhi. (2023). Implementation of Enhanced Recovery After Caesarean Surgery as a Leading Program at Hospital X in Jombang, East Java: A SWOT Analysis. Journal Multilingual , 3(4), 97-109.Neliti, 2019. "Impact of Clinical Pathway on Hospital Costs and Length of Stay."Nugraha, AC, Syaodih, E., Handayani, N., & Andikarya, RO (2023). The effect of health service quality on patient satisfaction and loyalty at Rama Hadi Hospital, Purwakarta . e-Proceedings of the Master of Management, ARS University, 1(1), 95-106.Nurdin, FW, Purwadhi, & Agung, IW (2023). Evaluation of Clinical Pathway Implementation in Pneumonia Cases in the Internal Medicine Inpatient Unit at Risa Sentra Medika Hospital, Mataram with the Integrated Care Pathway Appraisal Tool (ICPAT) Method . Journal of Health Policy and Management, 8(1), 30-38. https://doi.org/10.26911/thejhpm.2023.08.01.04Page, MJ, Moher, D., Bossuyt, PM, Boutron, I., Hoffmann, TC, Mulrow, CD, Shamseer, L., Tetzlaff, JM, Akl, EA, Brennan, SE, Chou, R., Glanville, J., Grimshaw, J.M., Hróbjartsson, A., Lalu, M.M., Li, T., Loder, E.W., Mayo-Wilson, E., Mcdonald, S., … Mckenzie, J.E. (2020). Supplementary Material to: PRISMA 2020 explanation and elaboration: updated guidance and exemplars for reporting systematic reviews . BMJ, 372 – 372.<span style="font-family: 'Arial Narrow',sans-serif; mso-fareast-font-family: 'Arial Narrow'; mso-bidi-font-family: